Novel mutations in GJB1 trigger intracellular aggregation and stress granule formation in X-linked Charcot-Marie-Tooth Disease - Chu, Fan; Xu, Jiaming; Wang, Yong; Li, Yingjie; Wang, Yaling; Liu, Zhijun; Li, Chuanzhou (Frontiers in Neuroscience, 2022)
X-linked Charcot-Marie-Tooth Disease type 1(CMT1X) is the second most common form of inherited peripheral neuropathy that is caused by mutations in the gap junction beta-1 (GJB1) gene. Using targeted exome-sequencing, we investigated 4 CMT families from central-southern China, and identified 2 novel missense variants (p.F31S and p.W44G) and 2 previously reported variants (p.R220Pfs*23 and p.R164Q) of GJB1. All 4 probands presented typical early-onset peripheral neuropathy, of which the R220Pfs*23 carrier also had neurologic manifestations in the central nervous system. We then constructed GJB1 expression vectors and performed cell biological analysis in vitro. Expression of FLAG-tagged GJB1 at various time points after transfection revealed evident protein aggregation with both wild-type and mutant forms, indicated with immunostaining and immunoblotting. Detergent based sequential fractionation confirmed that all mutants were higher expressed and more prone to aggregate than the wild-type, whereas the R220Pfs*23 mutant showed greatest amount of SDS-soluble multimers and monomers among groups. Moreover, intracellular aggregation probably occurs in the endoplasmic reticulum compartment rather than the Golgi apparatus. Gap junction-plaques were present in all groups and was only compromised in frameshift mutant., Further evidence reveals significant intracellular stress granule formation induced by mutated GJB1 and impaired cell viablitiy indicative of cytotoxicity of self-aggregates. Together, our findings demonostrate novel GJB1 variants-induced cell stress and dysfunction and provide insights in understanding the pathomechanisms of GJB1-CMTX1 and other related disorders.